Assay Characteristics Influence the Aldosterone to Renin Ratio as a Screening Tool for Primary Aldosteronism: Results of the German Conn’s Registry - Fischer, E.; Reuschl, S.; Quinkler, M.; Rump, L. C.; Hahner, S.; Bidlingmaier, M.; Reincke, M.; null (Hormone and Metabolic Research, 2013)
Primary aldosteronism (PA) is the most frequent cause of secondary arterial hypertension. The aldosterone to renin ratio (ARR) is the gold standard for screening, but variability between biochemical methods used remains of concern. The aim of the study was to analyze center-specific features of biochemical diagnostic strategies prior to the 2008 consensus within the German Conn’s Registry. The study was designed as a retrospective study in 5 tertiary care hospitals. Patients analyzed for PA between 1990 and 2006 were studied. Characteristics of the assays used to determine ARR during establishing the diagnosis of PA were analyzed in the retrospective part of the German Conn’s Registry. Eighty-six out of 484 documented ARR values had to be excluded from further evaluations because the laboratory or the assays were unknown. In the remaining 398 patients ARR was determined using 10 different assay combinations in the centers (aldosterone plus plasma renin activity or concentration). Considerable differences were seen between the mean concentrations for aldosterone (p<0.0001), renin concentration (p<0.001), and renin activity (p=0.009) for the different assays. The differences between the absolute concentrations measured by the different assays also had significant impact upon the resulting mean ratios. If published cutoff values are applied, the use of different commercial assays to determine the ARR in clinical routine results in major differences in positive screening rates. This heterogeneity affects sensitivity and specificity of screening for PA. Our data emphasize the importance of standardized screening procedures, which must include standardization of biochemical methods.
Keywords: primary aldosteronism; aldosterone; renin; aldosterone to renin ratio; screening; assay